2008
DOI: 10.1002/adma.200800830
|View full text |Cite
|
Sign up to set email alerts
|

Converting Metallic Single‐Walled Carbon Nanotubes into Semiconductors by Boron/Nitrogen Co‐Doping

Abstract: Electronic transport measurements on boron/nitrogen co‐doped single‐walled carbon nanotubes (BCN‐SWNTs) have been performed to determine their metallic or semiconducting character. The results obtained from a large number of BCN‐SWNT‐based field‐effect transistors indicate that the as‐grown BCN‐SWNTs are purely semiconducting, while the undoped C‐SWNTs consist of only about 70% semiconducting nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 23 publications
(23 reference statements)
12
51
1
Order By: Relevance
“…39͑b͒. The dash-dotted line shows the RPA absorption spectrum, which is in agreement with RPA calculations ͑Strinati, 1984; Xu and Ching, 1991;Guo and Lin, 2005͒. The broad peak with a maximum at 5.6 eV is entirely due to the continuum of interband transitions between the and * bands ͑see Fig.…”
Section: Excitonic Effectssupporting
confidence: 67%
See 1 more Smart Citation
“…39͑b͒. The dash-dotted line shows the RPA absorption spectrum, which is in agreement with RPA calculations ͑Strinati, 1984; Xu and Ching, 1991;Guo and Lin, 2005͒. The broad peak with a maximum at 5.6 eV is entirely due to the continuum of interband transitions between the and * bands ͑see Fig.…”
Section: Excitonic Effectssupporting
confidence: 67%
“…Reports on experiments with SWNTs are few so far. However, some work has recently appeared, such as the experiment by Xu, Lu, et al ͑2008͒, who suggested the possibility of converting metallic C-SWNTs into semiconductors by B and N codoping. They probed this by, making field-effect transistors devices, and later performed ab initio calculations of the structures with the doping levels obtained experimentally ͑between 3 and 8 at.…”
Section: Transportmentioning
confidence: 99%
“…Precursors containing carbon and hetero atoms are introduced simultaneously and then deposited onto the surface of the nanochannels, thus yielding outer surface doped CNTs. N and B are the most widely used hetero atoms for the doping of CNTs [102][103][104][105].…”
Section: Hetero Atom Doping Of the Aao-cntsmentioning
confidence: 99%
“…Much attention has been paid on the modification of the mechanical and electrical properties of carbon nanotubes (CNTs) by various manipulations, e.g., strain engineering, [1][2][3] non-covalent functionalization, [4][5][6] chemical doping, 7 etc. By such manipulations, people have observed large number of new phenomena that are significant for wide range of potential applications of new nano devices.…”
Section: Introductionmentioning
confidence: 99%